A UPLC-MS/MS method reveals the pharmacokinetics and metabolism characteristics of kaempferol in rats under hypoxia. (April 2022) - Li, Jing; Wu, Yi; Ma, Yi; Bai, Lu; Li, Qiang; Zhou, Xuelin; Xu, Pingxiang; Li, Xiaorong; Xue, Ming
Abstract: As a natural flavonoid, kaempferol is widely distributed in natural medicines. Our study was aimed at analyzing and comparing the pharmacokinetic differences of kaempferol between normoxia and hypoxia in rats, to further explore the effect of hypoxia on drug metabolism enzymes. A sensitive UPLC-MS/MS method was established and validated for the determination of kaempferol in rat plasma. The results indicated that AUC, MRT, t1/2 and Cmax of kaempferol significantly increased and the clearance reduced in hypoxic rats. Based on the comparison of pharmacokinetics, the metabolites of kaempferol in hypoxic rats were identified by using UPLC-QTOF-MS and UNIFI 1.8 software. Then we explored the effect of hypoxia on the mRNA and protein expression of CYP1A2 and UGT1A9. The study revealed that hypoxia could markedly reduce the mRNA and protein expression of CYP1A2 and UGT1A9, resulting in the reduction of metabolic rate and enhancement of systematic exposure. Our data also indicated that we should pay attention to adjusting the dosage regimen and reducing drug interactions when drugs metabolized by CYP1A2 and UGT1A9 are used in combination with kaempferol. Our findings suggested the potential requirement for dose adjustment of kaempferol or its structural analogs in hypoxic condition.